(untitled) (Bangladesh Journal of Livestock Research, 2016)
This study was aimed to evaluate milk urea nitrogen (MUN) of cows considering variations in dietary nutrition, genetic quality and lactation yield which will be helpful to develop practical feeding guidelines for dairy cows based on MUN. A total of forty dairy cows consisting 20 native and 20 crossbred milking cows were selected in Sonaimuri, Noakhali in winter season to know the daily feed availability to cows. Feed, milk and blood samples were collected and analyzed. The dry matter intake of the local and crossbred cows were 2.58 and 2.74 (g/100 kg live weight respectively) and they did not show statistical variation (p<0.05). Metabolizable energy (ME) and protein intake showed significantly higher values in crossbred (85 MJ/day and 815 g/day) compared to local (40 MJ/day and 395 g/day) cows in winter season (p>0.05). Live weight, body condition score and milk yield and MUN varied significantly between genotypes although blood urea nitrogen (BUN) value did not differ significantly. Strong correlation between lactose and protein percentage was observed in both the lactations in local cows. Milk minerals are negatively correlated with protein, SnF and minerals in first lactation whereas moderate to strong relation was observed in second lactation with those parameters. Milk constituents didnt show any difference between local & crossbred cows. Strong correlation between milk protein and lactose with SnF were observed in both local and crossbred cows in first lactation stage. BUN value showed a moderate correlation between milk yields of local cows. The results revealed that genotype and lactation have no effect on BUN although MUN value showed significant difference between local and crossbred cows. Bangladesh J. of Livestock Res. 19(1-2): 74-84, Jan-Dec 2012